Development of Self-Nanoemulsifying Drug Delivery Systems Containing 4-Allylpyrocatechol for Treatment of Oral Infections Caused by Candida albicans - Siriporn Okonogi; Pimpak Phumat; Sakornrat Khongkhunthian; Pisaisit Chaijareenont; Thomas Rades; Anette Müllertz (Pharmaceutics, 2021)
Clinical use of 4-Allylpyrocatechol (APC), a potential antifungal agent from Piper betle, is limited because of its low water solubility. The current study explores the development of the self-nanoemulsifying drug delivery system (SNEDDS) containing APC (APC-SNEDDS) to enhance APC solubility. Results demonstrated that excipient type and concentration played an important role in the solubility of APC in the obtained SNEEDS. SNEDDS, comprising 20% Miglyol 812N, 30% Maisine 35-1, 40% Kolliphor RH40, and 10% absolute ethanol, provided the highest loading capacity and significantly increased water solubility of APC. Oil-in-water nanoemulsions (NE) with droplet sizes of less than 40 nm and a narrow size distribution were obtained after dispersing this APC-SNEDDS in water. The droplets had a negative zeta potential between −10 and −20 mV. The release kinetics of APC from APC-SNEDDS followed the Higuchi model. The NE containing 1.6 mg APC/mL had effective activity against Candida albicans with dose-dependent killing kinetics and was nontoxic to normal cells. The antifungal potential was similar to that of 1 mg nystatin/mL. These findings suggest that APC-SNEDDS are a useful system to enhance the apparent water solubility of APC and are a promising system for clinical treatment of oral infection caused by C. albicans.